Evolución y factores de pronóstico en cáncer diferenciado de tiroides - OSVALDO IRIBARREN B. (Revista Chilena de Cirugía, 2009)
Background: Differentiated thyroid carcinoma has a good prognosis with a 90% survival at 10 years. Follicular carcinoma is more aggressive than papillary carcinoma Aim: To study the clinical presentation, evolution and prognosis of differentiated thyroid carcinoma. Material and Methods: The pathological registries of differentiated thyroid cancer processed in a pathology service of a general hospital, between 1984 and 2007, were searched. The clinical records of patients were reviewed. Results: One hundred six pathology registries were identified but only 89 patients had complete medical records. Seventy six patients aged 44 ± 16 years had a papillary carcinoma and 13 patients aged 42 ± 15 years had a follicular carcinoma. After a mean follow up of 53 months, 65 patients with papillary and 12 patients with follicular thyroid cancer were alive. Five patients with papillary carcinoma and one with follicular carcinoma had a local or distant relapse. Calculated actuarial survival at 10 years was 84 and 100% for papillary and follicular carcinoma, respectively. Ten year survival for stage I, II, III and IV tumors was 100, 92, 68 and 0%, respectively. Mortality was associated with the presence of distant metastases, a stage IV tumor, vascular or lymphatic tumor infiltration, tumor size, lymph node involvement, extra capsular invasion and a multi focal lesions. The relative risk for mortality increases between 2.7 and 9 times with the presence of lymph node infiltration and distant metastases. Conclusions: The prognosis of differentiated thyroid cancer is related to lymph node infiltration and the presence of distant metastases.